THE IMPORTANCE OF EU-FUNDED PROJECTS FOR THE SUSTAINABLE DEVELOPMENT OF LOCAL COMMUNITIES - Nusa Lazar (Agora International Journal of Economical Sciences (AIJES), 2024)
Sustainable development has been one of the core strategies of the EU. The term refers to three basic components: the economic component, which is associated with balanced growth, the environmental component which refers to the preservation of the ecosystem, and the social component, which guarantees inter- and intra-generational equality. While talking about sustainability it is important also to tackle the topic of circular economy. The circular economy aims to preserve value by designing out waste and pollution, optimizing resources by keeping products and materials in use, and ensuring system effectiveness by regenerating natural systems. One of the strategies of the EU to achieve sustainable development and the move towards a circular economy is to support it through various EU-founded projects. In this article, we will elaborate on the current state of sustainable development of EU-founded schemes and how they can be used for different projects for local communities and cities since cities are seen as both the source and solution to today's economic, environmental, and social challenges. Furthermore, in the article, we will outline some best practices of EU-founded projects around sustainable development in the case of the city of Maribor, Slovenia, and indicate their importance for its community.
Keywords: 330